Discovery of DS79182026: A potent orally active hepcidin production inhibitor. Issue 16 (15th August 2017) - Fukuda, Takeshi; Goto, Riki; Kiho, Toshihiro; Ueda, Kenjiro; Muramatsu, Sumie; Hashimoto, Masami; Aki, Anri; Watanabe, Kengo; Tanaka, Naoki
Graphical abstract: Abstract: Hepcidin has emerged as the central regulatory molecule of systemic iron homeostasis. Inhibition of hepcidin could be a strategy favorable to treating anemia of chronic disease (ACD). We report herein the synthesis and structure-activity relationships (SARs) of a series of benzisoxazole compounds as orally active hepcidin production inhibitors. The optimization study of multi kinase inhibitor1 led to a potent and bioavailable hepcidin production inhibitor38 (DS79182026), which showed serum hepcidin lowering effects in a mouse IL-6 induced acute inflammatory model.